Don't bother putting leadership into people - Joseph A. Raelin (Academy of Management Perspectives, 2004)
Most leadership training that is being conducted in corporate offsites is ill-advised. I make this bold statement because the intent of most of this training is to put leadership into people such that they can transform themselves and then their organizations upon their return. In this article, I shall address why the latter process is unlikely to succeed and what alternatives exist that can more effectively put leadership directly into the organization, where it belongs.
Keywords: M10; M12; M53; O15; J28; M51; M14; 650; Leadership development; Collaboration; Leaderful practice; Shared leadership; Work-based learning; Action learning; Reflective practice; Leadership